Social Media security leveraging social networking while mitigating - Cross, Michael 1965- (Syngress, 2013)
This book will help an organization understand the risks present in social networks and provide a framework covering policy, training and technology to address those concerns and mitigate the risks presented to leverage social media in their organization. The book also acknowledges that many organizations have already exposed themselves to more risk than they think from social networking and offers strategies for "dialing it back" to retake control. Defines an organization's goals for social networking. Presents the risks present in social networking and how to mitigate themExplains how to maintain continuous social networking security